An automatic technique for selective feeding and logging of individual wild squirrels - Kenward, B; Kenward, R; Kacelnik, A (2005)
We describe an automated feeding station for squirrels which identifies individuals and logs their feeding times, using passive integrated transponders (PIT tags). The system can provide or deny food to tagged individuals based on identity and/or arbitrary schedules. We test the system with wild grey squirrels Sciurus carolinensis, and report their feeding patterns and their ability to learn to manipulate a joystick to gain access. Possible applications for the system include behavioural or ecological research where the food access of different free-ranging individuals is to be controlled, and the supplementary feeding of red squirrels Sciurus vulgaris.